Injecting service-orientation into multi-agent systems in industrial automation - Mendes, João M. (2010)
Service-oriented architecture and multi-agent systems are used in the research of novel control systems for industrial automation. This work presents the advance of service-orientation into multi-agent system in industrial automation. An overview of the concept of service-oriented agent is done and also the enhancements that services can bring to multi-agent systems. The documented topics of this work are based on the experiments and projects of the authors in the domain of distributed and component based automation systems. The outcome shows that there are many beneficts, namely the aspects of knowledge representation, communication, plug & play, interactions, beside others. These contribute to the vision of future automation systems, where flexibility and customization are strong arguments.